Associations Between Physical Activity and Preserved Ratio Impaired Spirometry: A Cross-Sectional NHANES Study - Fu X; Guo J; Gu X; Chen L; Ju J; Huang H (International Journal of COPD)
Xiaofang Fu,1,* JiangYing Guo,2,* Xiaofei Gu,1 Liyan Chen,1 Jiangang Ju,1 Huaqiong Huang2 1The First People’s Hospital of Hangzhou Linping District, Zhejiang University School of Medicine Second Affiliated Hospital Linping Hospital, Hangzhou, Zhejiang, People’s Republic of China; 2Key Laboratory of Respiratory Disease of Zhejiang Province, Department of Respiratory and Critical Care Medicine, The Second Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Huaqiong Huang, The Second Affiliated Hospital of Zhejiang University School of Medicine, Shangcheng District, Hangzhou, Zhejiang, 310009, People’s Republic of China, Tel +8615005818703, Email zr_hhq@zju.edu.cn Jiangang Ju, The First People’s Hospital of Hangzhou Linping District, Zhejiang University School of Medicine Second Affiliated Hospital Linping Hospital, Linping District, Hangzhou, Zhejiang, People’s Republic of China, Tel +8615372002070, Email LL0731QQ0516@163.comBackground: Preserved ratio impaired spirometry (PRISm) is considered to be one of the early chronic obstructive pulmonary disease states, and there are few studies on PRISm prevention. We aimed to evaluate the relationship between physical activity and the risk of PRISm.Methods: A cross-sectional study was conducted using data from US adults who participated in the National Health and Nutrition Examination Survey (NHANES) between 2007 and 2012. We examined the association between physical activity and PRISm using multivariable logistic regression models and a restricted cubic spline (RCS) model.Results: Compared to the normal and chronic obstructive pulmonary disease (COPD) groups, the PRISm group had lower levels of physical activity (3537.2 MET-min/week in the normal group vs 3452.1 MET-min/week in the COPD group vs 2841.5 MET-min/week in the PRISm group). Adjusted multivariable regression models revealed that greater physical activity dose (more than 4800 MET-min/week) was associated with lower odds of PRISm (adjusted odds ratio [aOR] = 0.77, 95% confidence interval [95% CI] = 0.61– 0.98; P = 0.031). The RCS curve revealed that there was a significant nonlinear negative dose–response relationship between the level of physical activity and the risk of PRISm (Pnon-linearity